Serial Investors and Early Stage Finance - Peter Kelly; Michael Hay (Journal of Entrepreneurial and Small Business Finance, 1996)
This study examines the early stage investment activity of UK serial investors, individuals who have made at least three private investments. Two distinct groups emerged; one which invested on their own all the time ("solo serial investors") and the other which invested with others almost exclusively ("syndicate serial investors"). Both groups had invested in a variety of industrial sectors, a majority of which were in sectors where no one in the investor group had previous direct experience. Concept familiarity appeared to be a necessary, albeit insufficient, prerequisite to the decision to invest. For a majority of the investments reviewed for both groups, the investor(s) backed individuals personally known to them, to another syndicate member, and/or to the deal referrer. When the linkage to performance is explored, both solo and syndicate serial investors are well advised to back entrepreneurs known to a least one member of the investor group.
Keywords: G24; M13; G31; 650; Serial Investors; Early Stage Finance